Sociolinguistic Competence, Linguistic Intelligence and Self-Efficacy in Teaching Filipino: Input to Pedagogical Enhancement in National High Schools of Capiz - Avila, Ricaflor (International Journal of Arts, Sciences and Education, 2023)
Sociolinguistic Competence, linguistic intelligence, and Self-Efficacy in Teaching Filipino: Input to Pedagogical Enhancement in National High Schools of Capiz Ricaflor R. Avila Filamer Christian University ricaforavila20@gmail.com Abstract Sociolinguistic competence and linguistic intelligence are two of the most important pedagogical skills a Filipino teacher should possess along with self-efficacy in teaching Filipino subjects. This mixed-method research aims to determine the relationship of sociolinguistic competence and linguistic intelligence to self-efficacy in teaching Filipino in secondary schools of the Department of Education in the Province of Capiz, School Year 2022-2023. Utilizing stratified random sampling, 210 Filipino teachers in the secondary level were selected as the respondents of the study. It was conducted in Capiz Division, composed of 17 districts, and Roxas City Division. Sociolinguistic competence was measured using a researcher-made questionnaire with reliability index of 0.92 while the self-efficacy was measured using the revised Bandura’s Standardized instrument with a reliability index of 0.92. Focused Group Discussion (FGD) was conducted to gather in-depth qualitative data using Focused Group Discussion Guide which also had passed face and content validation. Quantitative data were analyzed with the use of frequency counts, means, standard deviations, Pearson r Correlation. Overall, Filipino teachers in the secondary level had “very high” level of sociolinguistic competence; “good” in their linguistic intelligence; and had “very high” level of self-efficacy in teaching Filipino. There was a significant relationship between the sociolinguistic competence and self-efficacy of the Filipino teachers. To address the gap discovered from the results of the study, a Training Course Design for Filipino Teachers was developed. Keywords: Sociolinguistic competence, self- efficacy, Filipino teachers, DepEd secondary level